Comprehensive analysis of differences in cashmere production performance in Liaoning cashmere goats by using metabolomics and transcriptomics - Luo, Bing; Wang, Meiqi; Han, Di; Wang, Chunqiang; Ma, Wei (Frontiers in Veterinary Science, 2025)
IntroductionThe Liaoning cashmere goat is a precious dual-purpose breed in China. Although cashmere yield has improved through years of selective breeding, there remains potential for further enhancement. A subset of these goats exhibits a perennial long-wool (PT-LCG) trait, characterized by higher cashmere yield and an extended fiber growth cycle, whereas others display a seasonal long-wool (ST-LCG) pattern. The molecular mechanisms underlying these distinct traits are not yet fully understood.MethodsSkin tissue samples were collected from six female PT-LCG and six ST-LCG goats during the catagen phase (November). Histological structure of secondary hair follicles (SHFs) was examined via H&E staining. Untargeted metabolomic profiling was performed using gas chromatography-mass spectrometry (GC-MS) to identify differentially expressed metabolites (DEMs) and KEGG pathway enrichment. Transcriptome sequencing (RNA-seq) was conducted on the Illumina platform to identify differentially expressed genes (DEGs), followed by Gene Ontology (GO) and KEGG enrichment analyses. Key DEGs were validated by qRT-PCR. Integrated multi-omics analysis was employed to explore metabolite-gene interactions.ResultsHistological observation revealed no significant structural differences in SHFs between the two types during catagen; however, PT-LCG showed higher SHF activity. Metabolomics identified 92 DEMs (67 up- and 25 down-regulated), primarily enriched in lipid metabolism, amino acid metabolism, and energy metabolism pathways. Key metabolites such as 3-hydroxypropionic acid and multiple long-chain fatty acids were significantly up-regulated in PT-LCG. Transcriptomic analysis revealed 145 DEGs (28 up- and 117 down-regulated), significantly enriched in lipid metabolism, extracellular matrix (ECM) organization, and inflammatory pathways including PPAR and IL-17 signaling. Integrated analysis uncovered a synergistic “metabolite–receptor–gene” network, indicating that lipid metabolism, energy supply, and ECM remodeling are crucial for maintaining follicle activity in PT-LCG. qRT-PCR confirmed the reliability of the RNA-seq data.DiscussionThis study reveals the molecular basis for prolonged hair follicle activity in PT-LCG through integrated transcriptomic and metabolomic analysis. PT-LCG likely sustains continuous cashmere growth by enhancing lipid synthesis and storage, remodeling the ECM for structural support, and modulating inflammatory signaling such as the IL-17 pathway to maintain follicular microenvironment homeostasis. These findings provide new insights into the regulation of the hair follicle cycle in mammals and offer valuable candidate targets for molecular breeding aimed at improving cashmere yield and quality.